Analisis Kebijakan Pendidikan Negara-negara ASEAN dalam Mendukung Suistanable Developments Goal - Khaidir Fadil; Suhendra Suhendra; Amran Amran (Pendidikan Agama Islam STIT Palapa Nusantara, 2023)
The purpose of this study was to determine education policies that support quality education SDGs in several ASEAN countries, especially Indonesia. The method used is library research by taking references from books, websites, and international journals. Sustainable Development Goals or commonly abbreviated SDGs are sustainable development goals resulting from the UN Summit in 2012. One of the 17 resulting goals is regarding quality education. Several ASEAN countries such as Singapore, Malaysia, Brunei Darussalam, and Indonesia have demonstrated that education policies have been issued to support quality education SDGs. In Singapore, it is proven by ensuring that all children of Singapore Citizens over the age of six must be enrolled in a national primary school. The six-year primary school education, which is heavily subsidized, aims to provide Singaporean children with a general core of knowledge that serves as a solid foundation for further education and training. While it is proven by the policies and priorities of education in Malaysia which are systematically related to the national development plan. As such, the ministry of education is committed to providing education and training services in line with the main thrust of the National Line Perspective Plan and the 5-Year Development Plan. Then, in Brunei Darussalam, it was proven that Through the '2018-2022 Strategic Plan', the ministry of education has set its mission to provide holistic education to achieve maximum potential for all in line with its vision of 'Quality Education, Dynamic Nation'. Whereas in Indonesia the implementation of quality education policies in support of the SDGs can be seen based on reports of regional action plans, one of which is West Java and East Java, namely: Increasing lifelong learning opportunities for all people free of charge, equal and quality which leads to the achievement of effective and relevant learning. while basic services are of high quality. Namely free quality education and health Tis-Tas (Free and Quality)